Determination of chiral bioactive molecules in Justicia adhatoda leaves by GC–MS. Issue 11 (31st August 2022) - Das, Anuradha; Ghosh, Shyamasree
Abstract: Chiral compounds find importance as drugs and therapeutic targets. Enantiomers of chiral drugs have been found to show different biological properties like pharmacokinetics, toxicology, pharmacology, metabolism, and so forth. In this study, we have identified the chiral compounds present in the medicinal plant Adhatoda vasica Nees ( Justicia adhatoda Linn). Phytochemical investigation on the leaves of Justicia adhatoda resulted in the identification of 27 chiral compounds. We report diverse compounds identified in the crude methanolic extract of Justicia adhatoda leaves by GC–MS analysis exhibiting diverse biological activities. Quantitative analysis of anticancer compound dihydroxycolchicine from the methanolic extract of J. adhatoda leaves was done by external standard method, and the amount of anticancer compound dihydroxycolchicine was found to be 87.823 mg/l indicative of moderate production in the leaves. Therefore, the extract of leaves of Justicia adhatoda can be used as a potential source of chiral bioactive molecules of pharmacological importance for drug synthesis. Abstract :